Diagnostic Value of Free Prostate-Specific Antigen among Men with a Prostate-Specific Antigen Level of <3.0μg per Liter - Finne, Patrik; Auvinen, Anssi; Määttänen, Liisa; Tammela, Teuvo L.; Ruutu, Mirja; Juusela, Harri; Martikainen, Paula; Hakama, Matti; Stenman, Ulf-Håkan (European urology, 2008)
The percentage of free prostate-specific antigen (%fPSA) improves the diagnostic accuracy for prostate cancer when the serum level of total PSA (tPSA) is elevated. Approximately 14% of men with a tPSA below 3μg/l have prostate cancer on biopsy, but the diagnostic value of %fPSA in such men is rather unknown. The purpose was to estimate the impact of %fPSA on future prostate cancer risk among men with a normal tPSA in prostate cancer screening. The first round of the Finnish arm of the European Randomized Trial for Screening of Prostate Cancer in 1996 to 1999 comprised 20,793 men aged 55–67 yr. Screen-negative men (tPSA level below 3.0μg/l, n=17,680) were followed up until the end of 2003. Cumulative risk of prostate cancer was calculated as a function of %fPSA. During the median follow-up of 5.8 yr (range, 0–7.7 yr), 327 men were diagnosed with prostate cancer and 25% of them had a Gleason score of 7 or higher. Five years after the first screening, cumulative risk of prostate cancer was 1.7% (95%CI, 1.5–1.9%). Men with a %fPSA in the lowest quartile (<14.2%) showed a 6.9-fold risk compared with those with a level in the highest quartile (>23.7%). In men with a low serum tPSA, a low %fPSA is a strong predictor of later diagnosis of prostate cancer. The diagnostic value of serum free PSA among men with low PSA values is unknown. A large screening study shows that percentage of free PSA predicts prostate cancer strongly and independently in men with total PSA lower than 3μg/l.